2020
DOI: 10.3168/jds.2019-17482
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and genomic analysis of long insemination interval in Israeli dairy cattle as an indicator of early abortions

Abstract: One of the causes of observed low fertility is embryo loss after fertilization. Previous findings suggested that more than half of fertilizations result in embryo loss before pregnancy is detected. We proposed reinsemination between 49 and 100 d after the first insemination as an indicator trait for early abortion (EA) in dairy cattle based on the mean estrus interval of 21 d. This trait was compared with conception rate from first insemination and conception status, computed as the inverse of the number of in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
1
12
2
Order By: Relevance
“…A total of 40,498 SNPs were retained. The GWAS files were prepared and formatted as described in Gershoni et al (2020Gershoni et al ( , 2021 and Weller et al (2021) using the Plink software (Purcell et al, 2007). The response variable was the sires' transmitting abilities (half of the EBV) for AFI.…”
Section: Genomic Analysismentioning
confidence: 99%
“…A total of 40,498 SNPs were retained. The GWAS files were prepared and formatted as described in Gershoni et al (2020Gershoni et al ( , 2021 and Weller et al (2021) using the Plink software (Purcell et al, 2007). The response variable was the sires' transmitting abilities (half of the EBV) for AFI.…”
Section: Genomic Analysismentioning
confidence: 99%
“…Numerous factors may cause fetal loss, including infectious diseases, toxic agents, heat stress, and genetic factors. Indeed, previous studies have reported that there is a substantial genetic variation underlying fetal loss in dairy catlle 8 10 . Known genetic factors include lethal recessive alleles, such as complex vertebral malformation (CVM) and deficiency of uridine monophosphate synthase (DUMPS), and an increasing list of recessive haplotypes 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Known genetic factors include lethal recessive alleles, such as complex vertebral malformation (CVM) and deficiency of uridine monophosphate synthase (DUMPS), and an increasing list of recessive haplotypes 11 . Recently, Gershoni and colleagues identified ABCA9 gene as a candidate gene for early abortions in Israeli dairy cattle 10 . Interestingly, ABCA9 gene is located within an ATP-binding cassette (ABC) genes cluster on BTA19, and the ABC family is the major class of primary active transporters in the placenta.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic evaluations for first parity dystocia and calf mortality were compute by single-trait sire and maternal grandsire models, as described by [ 12 ]. The component traits in PD16 and their index coefficients are given in [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…A total of 40,498 SNPs were retained. GWAS were computed as described in [ 13 , 14 ]. The response variable was the sires’ transmitting abilities for YG.…”
Section: Methodsmentioning
confidence: 99%